Time-resolved photoelectron spectroscopy at surfaces - Aeschlimann, Martin; Bange, Jan Philipp; Bauer, Michael; Bovensiepen, Uwe; Elmers, Hans Joachim; Fauster, Thomas; Gierster, Lukas; Höfer, Ulrich; Huber, Rupert; Li, Andi; Li, Xintong; Mathias, Stefan; et al. (Surface Science, 2025)
Light is a preeminent spectroscopic tool for investigating the electronic structure of surfaces. Time-resolved photoelectron spectroscopy has mainly been developed in the last 30 years. It is therefore not surprising that the topic was hardly mentioned in the issue on “The first thirty years” of surface science. In the second thirty years, however, we have seen tremendous progress in the development of time-resolved photoelectron spectroscopy on surfaces. Femtosecond light pulses and advanced photoelectron detection schemes are increasingly being used to study the electronic structure and dynamics of occupied and unoccupied electronic states and dynamic processes such as the energy and momentum relaxation of electrons, charge transfer at interfaces and collective processes such as plasmonic excitation and optical field screening. Using spin- and time-resolved photoelectron spectroscopy, we were able to study ultrafast spin dynamics, electron–magnon scattering and spin structures in magnetic and topological materials. Light also provides photon energy as well as electric and magnetic fields that can influence molecular surface processes to steer surface photochemistry and hot-electron-driven catalysis. In addition, we can consider light as a chemical reagent that can alter the properties of matter by creating non-equilibrium states and ultrafast phase transitions in correlated materials through the coupling of electrons, phonons and spins. Electric fields have also been used to temporarily change the electronic structure. This opened up new methods and areas such as high harmonic generation, light wave electronics and attosecond physics. This overview certainly cannot cover all these interesting topics. But also as a testimony to the cohesion and constructive exchange in our ultrafast community, a number of colleagues have come together to share their expertise and views on the very vital field of dynamics at surfaces. Following the introduction, the interested reader will find a list of contributions and a brief summary in Section 1.3.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Dark exciton; Exciton dynamics; Femtomagnetism; Free-electron laser; Hot electron dynamics; Image-potential states; Interlayer exciton; Intervalley scattering; Magnons; Momentum microscope; Photostationary states; Plasmons; Scherzer theorem; Semiconductor heterostructures; Time-and spin-resolved photoemission; Time-resolved momentum microscopy; Time-resolved photoemission; Time-resolved photoemission electron microscopy; Ultrafast spin dynamics